Frugal U(1) X models with non-minimal flavor violation for b → sℓℓ anomalies and neutrino mixing - Disha Bhatia (Journal of High Energy Physics, 2022)
Abstract We analyze the class of models with an extra U(1) X gauge symmetry that can account for the b → sℓℓ anomalies by modifying the Wilson coefficients C 9e and C 9μ of the operators O 9 ℓ ≡ b ¯ γ μ P L s ℓ ¯ γ μ ℓ $$ O_{9\mathrm{\ell}}\equiv \left(\overline{b}{γ}_{μ }{P}_Ls\right)\left(\overline{\mathrm{\ell}}{γ}^{μ}\mathrm{\ell}\right) $$ from their standard model values. At the same time, these models generate appropriate quark mixing, and give rise to neutrino mixing via the Type-I seesaw mechanism. Apart from the gauge boson Z′, these frugal models only have three right-handed neutrinos for the seesaw mechanism, an additional SU(2) L scalar doublet for quark mixing, and a SM-singlet scalar that breaks the U(1) X symmetry. This set-up identifies a class of leptonic symmetries, and necessitates non-zero but equal charges for the first two quark generations. If the quark mixing beyond the standard model were CKM-like, all these symmetries would be ruled out by the latest flavor constraints on Wilson coefficients and collider constraints on Z′ parameters. However, we identify a single-parameter source of non-minimal flavor violation that allows a wider class of U(1) X symmetries to be compatible with all data. We show that the viable leptonic symmetries have to be of the form L e ± 3L μ − L τ or L e − 3L μ + L τ , and determine the (M Z′ , g Z′ ) parameter space that may be probed by the high-luminosity data at the LHC.